Integrating Scientific Studies and Education: A Strategic Approach to Enhancing Learning Quality and Innovation in Higher Education - Wang, Hong; Yujie Wei (International Journal of Education and Humanities, 2025)
To accelerate the development of a strong nation in education, science, and technology while achieving self-reliance in high-level scientific and technological advancements, the integrated "trinity" of education, science, and talent cultivation is necessary. This study focuses on the significance of integrating education and scientific studies in higher education, emphasizing the role of universities in fostering a holistic educational ecosystem. This study employs a descriptive analysis of policies and practices related to integrating science and education at the School of Food Science and Engineering, Nanjing University of Finance and Economics. Data were collected through a literature review, an analysis of the university's internal policies, and an evaluation of its study platforms, study teams, scientific projects, and study outcomes. The findings indicate that implementing the integration of study and education in this university has significantly contributed to enhancing the quality of learning and the effectiveness of study-based moral education. This approach supports students' academic development and strengthens graduates' competitiveness in emerging technologies. The key contribution of this study lies in mapping a model of study-education integration that can serve as a reference for other higher education institutions. Academically, the study highlights that collaboration between education and scientific studies is an effective strategy for improving learning quality, fostering innovation, and enhancing national competitiveness in the global knowledge-based economy